Analisis Strategi Pemasaran Digital Dalam Meningkatkan Brand Awareness Pada UMKM Kuliner Di Kota Manado - Lumentut, Devie Mathilda (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The rapid development of digital technology has significantly influenced marketing strategies, including in the Micro, Small, and Medium Enterprises (MSMEs) culinary sector. Bandung, as one of Indonesia's culinary hubs, presents a highly competitive business environment, making it crucial for entrepreneurs to optimize digital marketing strategies to enhance brand awareness. This study aims to analyze the effectiveness of digital marketing strategies implemented by culinary MSMEs in Bandung in building brand awareness among consumers. Employing a qualitative approach, data were collected through in-depth interviews with culinary MSME owners and observations of their digital marketing activities. The findings reveal that the utilization of social media, content-based marketing, and search engine optimization (SEO) are the most effective strategies for increasing brand awareness. Additionally, customer engagement through active interactions and innovative content presentation plays a significant role in the success of digital marketing efforts. This research provides recommendations for culinary MSMEs in Bandung to further optimize their digital strategies to improve competitiveness in the digital era.